Analysis of the evidence on the efficacy and safety of CYD-TDV dengue vaccine and its potential licensing and implementation through Mexico´s Universal Vaccination Program - Mauricio Hernández-Ávila (Salud Pública de México, 2016)
Dengue is a major global public health problem affecting Latin America and Mexico Prevention and control measures, focusing on epidemiological surveillance and vector control, have been partially effective and costly, thus, the development of a vaccine against dengue has created great expectations among health authorities and scientific communities worldwide. The CYD-TDV dengue vaccine produced by Sanofi-Pasteur is the only dengue vaccine evaluated in phase 3 controlled clinical trials. Notwithstanding the significant contribution to the development of a vaccine against dengue, the three phase 3 clinical studies of CYD-TDV and the meta-analysis of the long-term follow up of those studies, have provided evidence that this vaccine exhibited partial vaccine efficacy to protect against virologically confirmed dengue and lead to four considerations: a) adequate vaccine efficacy against dengue virus (DENV) infections 3 and 4, less vaccine efficacy against DENV 1 and no protection against infection by DENV 2; b) decreased vaccine efficacy in dengue seronegative individuals at the beginning of the vaccination; c) 83% and 90% protection against hospitalizations and severe forms of dengue, respectively, at 25 months follow-up; and d) increased hospitalization for dengue in the vaccinated group, in children under nine years of age at the time of vaccination, detected since the third year of follow-up. The benefit of the CYD-TDV vaccine can be summarized in the protection against infection by DENV 3 and 4, as well as protection for hospitalizations and severe cases in people over nine years, who have had previous dengue infection, working mainly as a booster. In this review we identified elements on efficacy and safety of this vaccine that must be taken into account in the licensing process and potential inclusion in the national vaccination program of Mexico. The available scientific evidence on the CYD-TDV vaccine shows merits, but also leads to relevant questions that should be answered to properly assess the safety profile of the product and the target populations of potential benefit. In this regard we consider it would be informative to complete the 6-year follow-up after starting vaccination, according to the company’s own study protocol recommended by the World Health Organization. As with any new vaccine, the potential licensing and implementation of the CYD-TDV as part of Mexico’s vaccination program, requires a clear definition of the balance between the expected benefits and risks. Particularly with a vaccine with variable efficacy and some signs of risk, in the probable case of licensing, the post-licensed period must involve the development of detailed protocols to immediately identify risks or any health event associated with vaccination.